2022
DOI: 10.3390/life12020179
|View full text |Cite
|
Sign up to set email alerts
|

Operative Management of Avascular Necrosis of the Femoral Head in Skeletally Immature Patients: A Systematic Review

Abstract: Purpose: Osteonecrosis of the femoral head (ONFH) is common in skeletally immature patients. The management of ONFH is controversial, with limited evidence and unpredictable results. This study systematically reviewed the current operative modalities and clinical outcomes of surgical management for ONFH in skeletally immature patients. Methods: The present study was conducted according to the PRISMA 2020 guidelines. PubMed, Google Scholar, Embase, and Web of Science databases were accessed in October 2021. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…Despite the numerous studies on SONFH, its pathology, pathogenesis and efficacy remain unclear [ 27 ]. Once the necrosis of the femoral head occurred, most of the outcome of the lesion progression would be the collapse of the femoral head to different degrees, which would affect the hip function, and some patients would require surgical techniques to prevent or delay the collapse of the femoral head and secondary hip degeneration [ 28 ], such as core decompression [ 29 ], core decompression combined with bone marrow-derived cell therapies [ 30 ] or osteotomy [ 31 ], and even eventually undergo artificial joint replacement [ 5 ]. At present, there was still no completely satisfactory way to treat SONFH, and early diagnosis, early reasonable and effective treatment might be the best way to preserve the patient's own hip as possible at the current technological level.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous studies on SONFH, its pathology, pathogenesis and efficacy remain unclear [ 27 ]. Once the necrosis of the femoral head occurred, most of the outcome of the lesion progression would be the collapse of the femoral head to different degrees, which would affect the hip function, and some patients would require surgical techniques to prevent or delay the collapse of the femoral head and secondary hip degeneration [ 28 ], such as core decompression [ 29 ], core decompression combined with bone marrow-derived cell therapies [ 30 ] or osteotomy [ 31 ], and even eventually undergo artificial joint replacement [ 5 ]. At present, there was still no completely satisfactory way to treat SONFH, and early diagnosis, early reasonable and effective treatment might be the best way to preserve the patient's own hip as possible at the current technological level.…”
Section: Discussionmentioning
confidence: 99%
“…Sadile et al conducted a meta-analysis of 12 studies with a total of 776 patients and found that core decompression did not significantly delay the occurrence of hip osteoarthritis compared with other hip preservation treatments and the choice of surgical modality should be based on the situation of venous stasis and artery insufficiency [ 24 ]. However, Migliorini et al found that several hip-preserving surgical modalities (osteotomy; non-vascularised bone grafting; multiple epiphyseal drilling; and free vascularised fibular graft) were available and effective for ONFH in patients with skeletal immature [ 25 ]. At the same time, Marco’s recent study showed that about one-third of patients undergoes a THA by 7 years after the osteotomy, and THA after osteotomy failed has higher technical requirements [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first symptom is pain in the hip, which tends to be in proportion with lesion size, and in general precedes the beginning of femoral head collapse, which occurs on average after 8 months [ 23 , 24 ]. At the moment of hip pain and dysfunction, and obvious osteonecrosis and collapse of the femoral head appear in pathological and imaging examinations, in which case surgical treatment is badly needed [ 25 ]. With the wide application of bioinformatics and the continuous development of microarray technology at the genome level, researchers have sequenced more and more disease samples with increasing fragment information, and the public functional genomics database has been greatly enriched [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%